Circunstancialidade da invenção em A Varanda do Frangipani, de Mia Couto: entre a letra e a voz - Nascimento, Melquisedec Chaves do (2009)
This aims of this paper is to analyze the novel A Varanda do Frangipani by mozabican writer Mia Couto. Based on researches about orality made by Paul Zumthor, is researched some signs of performance through discursive strategies used by narrators. Such concept presented by Zumthor relates a virtual performance on the space of enunciation. In this perspective, orality is in the place of vocality, because is looked in this paper, not traces of speaks that could signs a frequent use in some communities, but virtual gestures presents in the discourse, that could be possible to realize in the phenomenon of reading and listening. For this reason, the reader is like a performer of the work s art, he is co-author of the work. The general hypothesis signs that a discourse of A Varanda do Frangipani is crowded of vocal and performing gestures. The first chapter, entitled Between letter and voice , is presented the concept of performance. That concept supports the general hypothesis. The reader, in face of the literary text, as well is object of discussion in this chapter: a previous deal between the reader and the work possibilities himself to live the performance. In this chapter is presented a literary biography of Mia Couto. In the second chapter, entitled, Collective Memory and the discursive space , is discussed the difference between orality and write, mainly based at the Walter Ong s researches: these both modalities has distinct traces, and it could be understood through of the own logic and under in a cultural perception point of view. Still is discussed how is the discursive space where there are reader and listener. In the last chapter, From the voice that sing to the word that tells , is presented a critical fortune about Mia Couto s work under three different perspectives, such critical relates different ways to treat the orality in Mia Couto s work. Finally, is made the analysis of novel through of the narrator voices. The present paper signs that there there are in the enunciation s virtual space: author, narrator, reader-listener, allows what Zumthor calls performance: A Varanda do Frangipani novel is virtually act. This is possible based in the enunciative context realized by reader/listener, that, despite of narrator silence, are present gestures, looking, movements, lapse, irony